Considerable mortality and morbidity in neonates born below 500 gram. (19th May 2021) - Goeral, Katharina; Fuiko, Renate; Binder, Julia; Lindtner, Claudia; Jernej, Raphaela; Rittenschober‐Boehm, Judith; Klebermass‐Schrehof, Katrin; Berger, Angelika; Grill, Agnes
Abstract: Data evaluating mortality and morbidity in infants born ≤500 g are scarce and show wide variability. To support counselling and decision‐making, we analysed neurodevelopmental outcome in all neonates ≤500 g birth weight. Retrospective analysis including preterm infants with a birth weight ≤500 g and a gestational age >22 weeks born at a single tertiary perinatal centre between 2010 and 2017. Of 59 live births, 88% received standard care. Birth weight ranged from 318 to 500 g and gestational age from 23 to 29 weeks. 56% of neonates were born ≤3rd percentile and 42% of treated infants survived. Neurodevelopmental outcome was available in 91% of patients and was evaluated using Bayley Scales of Infant Development at two years. 50% showed a favourable mental development (normal or mild impairment), 75% a favourable motor development and 45% a favourable outcome in both outcome subcategories. When additionally considering visual and hearing disability and, or, cerebral palsy level ≥2 according to the Gross Motor Function Classification System 35% had a good neurodevelopmental outcome. Survival rate was 37% for all live births and 42% for infants with standard care. More than one‐third of survivors showed no significant neurodevelopmental impairment at two years.